The Use of Syariah Fintech as An Alternative to SMEs Financing in West Java Province In Supporting Halal and Green Economy - Sartika, Dewi; Setyadi, Bakti; Jaya, Ade Kemala; Fitriasuri, Fitriasuri; Fitriyani, Rosha; Merdianto, Efran (International Journal of Community Service & Engagement, 2025)
This international community service activity aims to increase financial literacy and the use of syariah-based financial technology (fintech) for Micro, Small, and Medium Enterprises (MSMEs) in West Java Province. MSMEs have a great contribution to the national economy, but still face various obstacles such as limited access to financing, low understanding of financial management, and lack of awareness of halal and green economy principles. To answer these challenges, this program is designed through an educational and practical approach, in the form of training, mentoring, and cooperation with syariah fintech platforms. The material provided includes the concept of Islamic finance, how to access Islamic fintech services, and the integration of environmentally friendly principles in business activities. The results of the activity showed a significant increase in MSME actors' understanding of financial literacy and access to -based financing. In addition, there has been a shift in the mindset and behavior of business actors in managing finances that are more transparent and compliant, as well as the emergence of awareness of the importance of environmental sustainability. Some participating MSMEs have even started to implement an Islamic financial recording system and apply for financing through fintech platforms that suit their needs. This program proves that with the right education and sustainable support, MSMEs can transform into a more inclusive, ethical, and sustainability-oriented businesses.